Seaweed Farmers’ Interpretation of the Level of Their Children’s Formal Education in Lero Village, Suppa District, Pinrang Regency - Firdaus F; Hasriyanti H; Abdul Malik (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research is a quantitative research that aims to: 1) to know the socioeconomic background of seaweed farmers in Borongtala Village, Tamalatea Sub-district, Pinrang Regency. 2) find out how seaweed farmers' perceptions of children's formal education level in Borongtala Village, Tamalatea Sub-district, Pinrang Regency. The population in this study were 182 household heads. The sampling technique used the Snowball Sampling technique with a sample of 30 household heads. Data collection was carried out by means of observation, interviews, and documentation. Data analysis techniques using descriptive data analysis techniques. The results obtained from data analysis: 1. Social background: The education level of seaweed farmers is mostly at the primary level. And the condition of formal education of seaweed farmers' children stated that most seaweed farmers' children still continue their education at the primary level and secondary level. Economic background: The income level of the majority of seaweed farmers is still very low. And the average work expenditure of seaweed farmers used in working every day is 7-9 hours. 2. Seaweed farmers' perceptions of children's formal education levels in Borongtala Village are classified as good (Positive) because there are 60% of seaweed farmers have positive perceptions of children's formal education levels and 40% of seaweed farmers have negative perceptions of children's formal education levels.